The influence of socioeconomic position on patient-reported outcome measures following hip fractures – a register-based observational study on 35,206 patients from the Norwegian hip fracture register 2014–2018 - Cato Kjaervik; Jan-Erik Gjertsen; Eva Stensland; Jan Abel Olsen; Christer Kjaervik; Odd Soereide (Health and Quality of Life Outcomes)
Abstract Background Hip fractures are a significant public health concern due to increasing numbers, high mortality and negative impact on health-related quality of life (HRQoL). Socioeconomic position (SEP) affects various health outcomes, but the specific impact on HRQoL and satisfaction after hip fracture remains underexplored. This study assesses whether education and household income influence patient-reported outcome measures (PROMs) after hip fractures, measured by three visual analog scales: EQ-VAS, pain-VAS, and satisfaction-VAS. Methods This was a nationwide retrospective cohort study using linked data from the Norwegian Hip Fracture Register and Statistics Norway. PROMs assessed at 4, 12, and 36 months postoperatively in 35,206 hip fracture patients from 2015 to 2018 were included. The SEP data included household income and education levels. Covariance analyses were conducted to evaluate differences in mean VAS scores for general health (EQ-VAS), pain from the operated hip (Pain-VAS), and satisfaction with the result of the operation (Satisfaction-VAS). Analyses adjusted for age, sex, vital status, cognitive impairment, treatment type, and education or income when not used as independent variable. Results The study included 23,649 women (67.2%) and 11,557 men (32.8%) with median age 83 years. Lower education was linked to worse EQ-VAS and Pain-VAS scores at all follow-ups and to lower Satisfaction-VAS at 12 and 36 months in both unadjusted and adjusted analyses. Lowest level of income had significant lower EQ-VAS at all follow-ups, lower Pain-VAS at 12 months, and lower Satisfaction-VAS at 4 months. There were increasing differences in mean VAS-scores during follow-up. At 36 months the adjusted differences in mean EQ-VAS between highest and lowest level of income was − 2,51 (-4.04 -0.99). Differences across education levels were even stronger associated; -3.58 (-5.19 to -1.98). Mean differences in Pain-VAS between medium and low education compared to high were 4.30 (2.91 to 5.69) and 5.58 (4.08 to 7.08), respectively. Lower levels of education also had significant negative differences in Satisfaction-VAS at 36 months follow-up -4.06(-5.86 to -2.26). Conclusions Lower education and income were significantly associated with worse HRQoL and satisfaction after hip fracture. The clinical relevance of these findings warrants further investigation. Addressing SEP disparities should be integral to hip-fracture care strategies aiming to improve postoperative outcomes.